Tingkat Perkembangan Nematoda Puru Akar (Meloidogyne spp.) pada Berbagai Jenis Tanaman Tomat Menggunakan Pengendalian Ekstrak Daun Kirinyuh - KIKI AMELIA RAMADHANY; I MADE SUDANA; I DEWA PUTU SINGARSA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2021)
Development Rate of Root-Knot Nematode Meloidogyne spp. in Various Types of Tomato Plants Controlled with Siam Weed Extract The tomato plant, which is included in the Solanaceae family, is an annual herbaceous plant with a height between 70-200 cm, depending on the variety. Susenas (2012) reported that the average growth of tomato consumption in Indonesia in 2007-2011 is 2.1%. Based on data from the Central Statistics Agency (2005) in Taufik et al. (2014), tomato production in 2012 experienced a decrease in the amount of production from the previous year (2011), from 954,046 tons to 893,463 tons. Meanwhile, domestic demand for tomatoes in 2012 amounted to 904,000 tons, resulting in 10,537 tons of imported tomatoes (Pusdatin, 2014). One of the causes of the decline in tomato production is the disruption of plant pests, leading to failure. One of the diseases that attack tomatoes at all stages of growth is a root-knot disease caused by the nematode Meloidogyne spp. that live in plant nodules. Control of Meloidogyne spp. was done by using trap crops, crop rotation, and so on. In this study, we used biological control, using Siam weed leaf extract (Chromolaena Odorata L.). The results showed that the high level of development in tomato plant varieties could be known through the research data, including the number of roots and egg masses. The number of eggs indicated that the yellow cherry variety was higher than the varieties of red cherries, swadesi, serpo, and agata.